Directly converting cellulose into high yield sorbitol by tuning the electron structure of Ru2P anchored in agricultural straw biochar. (15th August 2022) - Qiu, Mo; Zheng, Junhao; Yao, Yuhang; Liu, Longxin; Zhou, Xiaomei; Jiao, Hui; Aarons, Jolyon; Zhang, Keqiang; Guan, Qingxin; Li, Wei
Abstract: Directly converting cellulose into sorbitol involves efficient synergy of cellulose hydrolysis and glucose hydrogenation in a bifunctional catalyst. High temperature is favorable and efficient for cellulose hydrolysis, but easily causes the excessive hydrogenation of sorbitol. In this paper, we propose a new strategy to appropriately regulate the hydrogenation activity of Ru catalysts by partially shifting the electrons from Ru to P, which could reduce excessive hydrogenation of sorbitol at 180–200 °C and thus enhance the sorbitol yield. The rice straw biochar was used as carrier and Ru2 P/C was synthesized for obtaining sorbitol from glucose by hydrogenation. Subsequently, the bifunctional catalyst Ru2 P/C–SO3 H was prepared for directly converting cellulose into sorbitol, and the relationship between the composition of the as-prepared catalyst and the sorbitol yield was systematically studied. Satisfactorily, 2 wt% Ru2 P/C–SO3 H gave sorbitol yields of 96% and 64% at 200 °C within 2 h when glucose and cellulose were used as raw materials, respectively. The characterization results and DFT calculations show that the electrons of Ru atoms in Ru2 P are partially transferred to P, which weakens the adsorption and activation of H2 and H* on Ru atoms, thus improving the selectivity of sorbitol. Moreover, Ru2 P/C–SO3 H has a potential ability in natural biomass waste utilization. Graphical abstract: Image 1 Highlights: Bifunctional Ru2 P/C–SO3 H was proposed to enhance sorbitol yield from cellulose. Hydrogenation activity of Ru2 P was regulated by tuning the electron structure of Ru. The electron shift of Ru atom weakens the adsorption and activation of H2 and H*. Ru2 P/C–SO3 H could reduce excessive hydrogenation of sorbitol at high temperature. It's a new strategy to design efficient catalyst in converting cellulose to sorbitol.